Association of dietary vitamin K1 intake with epilepsy in adults in US: a cross-sectional study of National Health and Nutrition Examination Survey 2013-2018 - Tiancong Chen; Baoquan Wang; Jinjing Lu; Li Jing (BMC, 2024)
Abstract Objective Information regarding the relationship between epilepsy and vitamin K1 remains unclear. We aimed to assess the association between dietary vitamin K1 intake and epilepsy. Methods Data was obtained from the National Health and Nutrition Examination Survey (NHANES) conducted from 2013 to 2018. The study enrolled participants aged ≥ 18 years that provided complete information on their dietary vitamin K1 intake and epilepsy status. Weighted multivariable regression and subgroup analyses were performed to detect the association between dietary vitamin K1 intake and epilepsy. Results In total, 10 137 participants (mean age, 48 years) were enrolled. Among them, 84 (0.83%) participants were identified as having epilepsy, whereas 10 053 (99.17%) were included in the non-epilepsy group, with an average dietary vitamin K1 intake of 67.2 ± 6.9 and 105.5 ± 1.5 µg/d, respectively. Each unit (10 µg/d) increase in vitamin K1 intake was associated with a 7% decrease in the odds of epilepsy (odds ratio = 0.93, 95% confidence interval: 0.88-0.98, p = 0.011). Multivariate logistic regression analysis revealed that participants in the higher quartile had lower odds of epilepsy than those in the first quartile of vitamin K1 intake. Subgroup analysis showed a stable and consistent inverse association between dietary vitamin K1 intake and epilepsy. Conclusion Higher dietary vitamin K1 intake was associated with lower incidence of epilepsy. Our study did not establish a cause-and-effect relationship. Further large-scale prospective studies and randomized trials are warranted to confirm our findings.